KONTROVERSI PERKAWINAN SESAMA JENIS DI HALMAHERA SELATAN: TINJAUAN HUKUM ISLAM DAN DAMPAKNYA TERHADAP MASYARAKAT - D. Sumaila, Bayu; Rauf Wajo, Abd.; Willy Dama, Riski (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Social beings created with two different genders, humans have a clear legal basis in running the institution of marriage, as stipulated in Law Number 1 of 1974 which has been updated to Law Number 16 of 2019. This study uses a normative juridical approach through the analysis of written legal materials. The results show that same-sex marriage that occurs in South Halmahera is not only contrary to the social values of the Indonesian people, but also violates the principles of marriage in the applicable positive law and religion. As a result, the marriage is legally considered null and void. In addition, the negligence of the parties who facilitate this marriage without fulfilling the legitimate administrative requirements shows a lack of thoroughness in applying the terms of marriage. As stated in Article 1 of the Marriage Law Number 1 of 1974, marriage is an innate bond between a man and a woman as husband and wife, with the aim of forming a happy and eternal family based on the One Godhead. Thus, this same-sex marriage is clearly contrary to the provisions of the law (Islam and the state), and its implementation results in losses for one of the parties and damages the legal order of marriage in Indonesia.